2011
DOI: 10.1055/s-0031-1287783
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Blockade of TNF-α does not Improve Insulin Resistance in Humans

Abstract: The purpose of this study was to determine whether long-term modulation of inflammatory activity by tumor necrosis factor (TNF)-α inhibitors has some influence on insulin resistance (IR). 16 active rheumatoid arthritis (RA) patients without CV risk factors treated with anti-TNF-α agents were included in this study. RA activity by disease activity score 28, IR by HOMA2-IR, body composition by impedance analysis, physical activity by accelerometry, abdominal fat distribution by magnetic resonance imaging, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
2
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 24 publications
6
46
2
4
Order By: Relevance
“…Similar magnitudes of change have been reported previously [13]. The effect of therapy on HOMA-IR has been less well studied [40], with most reporting the effect of TNFi alone, involving small established RA cohorts [19,20] or short-term follow-up [18]. Our study provides valuable longer-term data.…”
Section: Use Of Cvd Screening Questionnairessupporting
confidence: 84%
See 1 more Smart Citation
“…Similar magnitudes of change have been reported previously [13]. The effect of therapy on HOMA-IR has been less well studied [40], with most reporting the effect of TNFi alone, involving small established RA cohorts [19,20] or short-term follow-up [18]. Our study provides valuable longer-term data.…”
Section: Use Of Cvd Screening Questionnairessupporting
confidence: 84%
“…DMARDS appear to reduce TC/HDL-C [13,14], however, metaanalyses report conflicting results [15,16], suggesting a complex relationship. IR can be improved with DMARDs in established RA [17], but the effect of TNFi is unclear [18][19][20][21][22][23][24]. The limited data on NT-proBNP suggest improvement with TNFi [25].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies reported improved insulin sensitivity in infliximab-treated patients with rheumatoid arthritis, 185,186 other authors found that insulin resistance was not alleviated by antagonism of TNF-α. 187 Gonzalez-Gay et al 188 suggested that the effects may depend on the degree and severity of insulin resistance before the start of therapy, whereby the beneficial effect is observed in patients with the most severe disease.…”
Section: Tnf-α Antagonism In Autoimmune Diseasesmentioning
confidence: 99%
“…RA in humans has been associated with impaired insulin sensitivity and glucose tolerance [31]. High serum visfatin has adiponectin [20].…”
Section: Introductionmentioning
confidence: 99%